Dasometric characterization and structure of tree stands at Chapultepec Forest second section - Benavides Meza, Héctor M.; Fernández Grandizo, Diana Young (Instituto de Ecología, A.C., 2012)
Chapultepec Forest is the largest and most visited urban green area (UGA) of Mexico City and forthese reasons, the protection and conservation of this place is a relevant issue to maintain the generationof the environmental services and benefits that it provides. Despite the importance of this area, there is alack of information about the horizontal structure and indicators of the tree stands located in this place, aswell as for the rest of the UGA of the city and the country, although some floristic or sanitary conditionsstudies had been done in some of them. The aim of this paper was to determine the dendrological and dasometriccharacteristics of the stands at the 2nd section of Chapultepec Forest, according with the informationobtained from a total tree inventory, complemented with 111 sampling sites of 500 m2. The estimated meanof trees per site was 295/ha, the mean crown cover value was 27,19 m2 and the canopy cover in the areaexceeds 80% of the total surface. The mean basal area was 0,10 m2 and the stems occupied 0,32% of thetotal surface. This data will provide basic indicators for the 2nd section tree stands and a reference for futureresearch projects and characterization of UGA in the city. In addition, the information is basic to sustain themanagement that requires the urban forest of Mexico City.